PENGARUH PERUBAHAN KEWENANGAN ORGANISASI DAN BUDAYA ORGANISASI TERHADAP KINERJA PENYULUH KELUARGA BERENCANA DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING PADA BADAN KEPENDUDUKAN DAN KELUARGA BERENCANA NASIONAL (BKKBN) - Dwi Kurnia Delas O (2023)
In this study, organizational commitment is used as an intervening variable to examine how changes in organizational authority and culture affect the performance of Family Planning Counselors (PKB) at the National Population and Family Planning Board of Indonesia (BKKBN). This research aims to enhance PKB performance within the BKKBN by examining the relationship between PKB performance and the variables that can affect it, such as shifts in organizational authority, organizational culture, and organizational commitment. By distributing surveys to 400 participants, this research strategy collects primary data using quantitative methodologies. Descriptive and inferential data analysis was done using the Structural Equation Modeling (SEM) method and the Partial Least Square (PLS) method, which forms the basis of variance. According to the findings, changes in organizational leadership, organizational culture, and organizational commitment significantly and favorably affect family planning counselors' effectiveness. Changes in organizational authority and culture positively and significantly impact organizational commitment. Organizational commitment substantially has implications on the performance of PKB at BKKBN due to changes in organizational authority and culture.